CRITICAL DISCOURSE ANALYSIS: THEORY AND METHOD IN SOCIAL AND LITERARY FRAMEWORK - Roma Ulinnuha (Indonesian Journal of Applied Linguistics, 2013)
Abstract: Critical Discourse Analysis (CDA) serves as one of the tools to analyze the linguistic and the social. This article aims at investigating the relevance of ideas amongst CDA figures—Fairclough, Van Dijk, Wodak, and Kristeva—to both social and literary studies. This includes some significant points such as discourse, social practice, representation, power and intertextuality. The article shows, based on literary study, the aim of CDA applied linguistic aspect is to reveal the hidden in the analytical level of individual, institutional or social, i.e. domination and the abuse of power. CDA figures agreed to some extent that the complex interactions of discourse and social could not be analyzed, unless it utilized the approaches of linguistic and social. In the course of identity, for instance, CDA abridges the social and the linguistic realm. CDA, in this regard, mainly advocates the under-privileged representations of everyday life.